Navigating visa inequities: mobility as privilege in academia - 'You are not supposed to be here' - Devran Gülel (Global Social Challenges Journal, 2025)
This provocation critically examines the unequal terrain of academic mobility, its impact on knowledge production and on who has the right to be an agent of scientific knowledge. Drawing on personal experiences of more than 15 years (autoethnography) and through a critical feminist lens, this article interrogates how geopolitical hierarchies often shape the careers of scholars from the Global South through restricted mobility opportunities. By analysing visa regimes as political tools that control scientific knowledge production and dissemination, I argue that academic (im)mobility functions not as a neutral measure of merit but as a form of privilege structured by geopolitical hierarchies. The article provides qualitative evidence regarding visa application experiences and the financial, psychological and temporal tolls they impose on scholars from the Global South. This provocation calls for reimagining academic mobility that values diverse scientific knowledge contributions and creates more equitable conditions for participation in the academic world. Ultimately, this provocation challenges academic institutions in the Global North to recognise visa regimes as mechanisms of epistemic exclusion, and calls for concrete actions, such as policy reforms and institutional support mechanisms, to mitigate the challenges faced by Global South scholars.